2021
DOI: 10.1097/olq.0000000000001573
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Emergence of Primary and Secondary Syphilis Among Women of Reproductive Age in US Counties

Abstract: Background: Syphilis, a sexually transmitted infection that can cause severe congenital disease when not treated during pregnancy, is on the rise in the United States. Our objective was to identify US counties with elevated risk for emergence of primary and secondary (P&S) syphilis among women of reproductive age.Methods: Using syphilis case reports, we identified counties with no cases of P&S syphilis among women of reproductive age in 2017 and 1 case or more in 2018. Using county-level syphilis and sociodemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, this is the first report of the geospatial distribution of maternal syphilis in an African country using routinely collected health system data. This method has been extensively used to map the evolving problem of syphilis in pregnant women and their infants in both the United States ( 24 , 25 ) and Brazil ( 26–33 ). Leveraging routinely collected data in this way provides a return for investment on district-level data collection.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report of the geospatial distribution of maternal syphilis in an African country using routinely collected health system data. This method has been extensively used to map the evolving problem of syphilis in pregnant women and their infants in both the United States ( 24 , 25 ) and Brazil ( 26–33 ). Leveraging routinely collected data in this way provides a return for investment on district-level data collection.…”
Section: Discussionmentioning
confidence: 99%
“…In the U.S.A., state-level analyses have shown that states with higher percentages of impoverished residents have higher rates of P&S syphilis among MSM [ 35 ]. Nationwide analyses have used modeling to predict the U.S. counties most vulnerable to CS [ 36 ] and to the emergence of primary/secondary syphilis among women of reproductive age [ 37 ], while national CS hospitalization rates have been shown to be independently associated with geographic region in addition to other SDH [ 38 ]. Finally, in Chicago, researchers developed a composite scoring system known as the Sexual and Reproductive Health Burden Index, which used eight indicators of sexual and reproductive health (including the incidence of syphilis and other STIs, teen births, infant mortality, and low infant birthweight) to describe which communities in Chicago were most impacted by adverse sexual and reproductive health outcomes [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, there were 137 cases of P&S syphilis cases in Chicago (a large urban area) and 19 cases of CS, according to a Cook County Department of Public Health (CDPH) report [24]. Though clinical data are often reported in terms of P&S cases of syphilis, collected data suggest a likelihood that the number of latent cases of syphilis (identified by serologic testing) are about three times the number of cases of P&S syphilis cases [25].…”
mentioning
confidence: 99%